2009
DOI: 10.12968/ijtr.2009.16.5.42103
|View full text |Cite
|
Sign up to set email alerts
|

The concerns of older women during inpatient rehabilitation after fractured neck of femur

Abstract: Aims There have been many studies conducted on the impact of fractured neck of femur on older women, but they have not focused specifically on the psychosocial impact of this injury on the lives of previously independent older women. This pilot study aimed to explore the impact of fractured neck of femur on the lives of previously independent women, and identify their concerns when participating in inpatient rehabilitation following their fracture. Methods Semi-structured interviews were undertaken with five w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…As in previous studies, patients expressed concerns regarding their future, and how they will manage after discharge, and becoming a burden to significant others, which left them feeling worried and insecure [28,33]. A further study by Zid en et al reported that patients continue to experience these feelings of uncertainty at one month after discharge [34].…”
Section: Subcategoriesmentioning
confidence: 71%
“…As in previous studies, patients expressed concerns regarding their future, and how they will manage after discharge, and becoming a burden to significant others, which left them feeling worried and insecure [28,33]. A further study by Zid en et al reported that patients continue to experience these feelings of uncertainty at one month after discharge [34].…”
Section: Subcategoriesmentioning
confidence: 71%
“…Most studies have focused on the period immediately after injury; including how patients make sense of the acute injury and hospital experience [ 27 29 ], communication and information provision [ 30 , 31 ], interactions with others on the ward and management of acute pain [ 32 , 33 ]. Other studies have explored more contextual factors such as patients’ experience of the discharge process and transition of care [ 30 , 34 ], challenges patients experience to rehabilitation [ 28 , 30 , 32 , 35 ], as well as the importance of support from family and friends [ 27 , 30 , 34 , 35 ]. Long term rehabilitation and recovery are of particular concern to patients as they return home with the aim to minimise loss of independence [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%